Investigating the Reading Preferences of Second-grade Pupils through Creation Lessons - Diana-Crina Marin; Mușata-Dacia Bocoș (Babes-Bolyai University, 2024)
It is unanimously accepted that reading activities have positive effects on children's development. Recent research has shown that pupils' interest in reading activities could be enhanced by providing interesting and age-appropriate books. The purpose of the research is to determine whether it is beneficial to organize didactic activities in which pupils use their creativity to establish titles of attractive books for them. At the same time, we were interested in finding out whether pupils want to frequently participate in creative lessons based on story writing. All 54 second-grade pupils who have participated in our research mentioned that they enjoyed participating in the creation lessons, and would like to cooperate with other older peers in the process of writing the stories. The research revealed that could be beneficial to organize lessons based on stimulating students' creativity with the purpose of understanding the reading preferences of the primary school pupils.